2005
DOI: 10.1598/jaal.49.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Is Reading Fluency a Key for Successful High School Reading?

Abstract: Fluency has traditionally been viewed as a goal of reading taught and mastered in the elementary grades. This article challenges that notion by exploring reading fluency as a contributor to reading proficiency (and difficulty) among ninth‐grade students. The authors assessed reading fluency development among a large number of ninth graders and found a moderately strong correlation between fluency and overall reading proficiency as measured by a standardized achievement test. Moreover, a significant number of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
1
15

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(116 citation statements)
references
References 8 publications
9
91
1
15
Order By: Relevance
“…Much previous research has found that S/CRP increases reading speed (Ellis, 2003;Newell, 1990;Nishida, 2009;Ohtagaki & Ohmori, 1991;Tan & Nicholson, 1997), and improves reading fluency and comprehension of struggling students in reading (Jones, 2012;Kadota, 1982;Kiroglu & Demirel, 2012;Kowal, O'Cannel, O'Brien, & Bryant, 1975). Struggling readers, on the other hand, often do not understand where a meaningful phrase ends, and they do not understand the whole sentence (Ransinki et al, 2005), whereas advanced readers are able to read a text by chunking it into meaningful phrase units effortlessly because they understand the sentence structure. They are not only able to process reading materials on a surface basis but comprehend the deeper meanings of the materials.…”
Section: Slash/chunked Reading Practice (S/crp)mentioning
confidence: 99%
“…Much previous research has found that S/CRP increases reading speed (Ellis, 2003;Newell, 1990;Nishida, 2009;Ohtagaki & Ohmori, 1991;Tan & Nicholson, 1997), and improves reading fluency and comprehension of struggling students in reading (Jones, 2012;Kadota, 1982;Kiroglu & Demirel, 2012;Kowal, O'Cannel, O'Brien, & Bryant, 1975). Struggling readers, on the other hand, often do not understand where a meaningful phrase ends, and they do not understand the whole sentence (Ransinki et al, 2005), whereas advanced readers are able to read a text by chunking it into meaningful phrase units effortlessly because they understand the sentence structure. They are not only able to process reading materials on a surface basis but comprehend the deeper meanings of the materials.…”
Section: Slash/chunked Reading Practice (S/crp)mentioning
confidence: 99%
“…The reader should keep in mind that students attending the study school come from homes where Malayalam is the native language and where English is seldom spoken. These results suggest that in this particular English medium school, students have developed phonics knowledge and reading fluency skills to a very high level not seen in many U.S. schools (Lee, 2010;Paige, 2011;Paige & Magpuri-Lavell, 2011;Rasinski et al, 2005;Teale, 2009). While research suggests that English language learners (ELLs) often reach word reading skill levels that are commensurate with native language learners, the present study results suggest that this group of readers significantly exceeds the level typified by average attainment at the 50th percentile (Lesaux & Geva, 2006;Lesaux, Rupp, & Siegel, 2007).…”
Section: Discussionmentioning
confidence: 76%
“…La fluidez lectora ha sido definida como uno de los componentes fundamentales de la lectura (National Reading Panel, 2000;Snow, 2002); su influencia en la comprensión lectora ha estado muy centrada en el nivel inicial, sin embargo, aún es necesaria en el nivel secundario (Baker et al, 2014;Paige, Rasinski, Magpuri-Lavell, & Smith, 2014;Rasinski et al, 2016Rasinski et al, , 2005. Fuchs (2009) sugiere que se debe valorar la fluidez lectora conjuntamente con la comprensión lectora, para abarcar las dimensiones fundamentales de leer.…”
Section: Fluidez Lectoraunclassified